Experimental neurotransplantation treatment for hereditary cerebellar ataxias - Cendelin, Jan (Cerebellum & ataxias, 2016)
Hereditary cerebellar degenerations are a heterogeneous group of diseases often having a detrimental impact on patients' quality of life. Unfortunately, no sufficiently effective causal therapy is available for human patients at present. There are several therapies that have been shown to affect the pathogenetic process and thereby to delay the progress of the disease in mouse models of cerebellar ataxias. The second experimental therapeutic approach for hereditary cerebellar ataxias is neurotransplantation. Grafted cells might provide an effect via delivery of a scarce neurotransmitter, substitution of lost cells if functionally integrated and rescue or trophic support of degenerating cells. The results of cerebellar transplantation research over the past 30 years are reviewed here and potential benefits and limitations of neurotransplantation therapy are discussed.
Keywords: Neurotransplantation; Cerebellum; Hereditary cerebellar degeneration